(untitled) (Boletin Médico de Postgrado, 2020)
Cytomegalovirus (CMV) infection is considered the most common cause of viral infection in pregnant women, the fetus and newborn. With the aim of describing the clinical profile of congenital cytomegalovirus infection in patients admitted in the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga during the 2012-2016 period, we conducted a retrospective study selecting 33 clinical histories to review; 60.6% of patients had congenital CMV infection while 39.3% had TORCH syndrome. 63.6% of patients were < 7 days at the moment of diagnosis, predominantly male (63.6%), with a gestational age < 36 weeks (69.7%) and a birth weight between 2501-3000 grs (51.5%). The average age of diagnosis was 17.9 ± 10.4 days; 96.9% of patients had jaundice, petechial rash (42.4%), enteritis and hepatosplenomegaly (27.2%, respectively). Hyperbilirubinemia was found in 96,9% of patients, leukocytosis in 72,7%, thrombocytopenia in 81.8% and high glutamic oxalacetic and pyruvic transaminase levels in 78.7% and 42.4% of cases. 96.9% of cases reported positive blood PCR, 18.1% positive PCR in urine and 3% positive IgM. Only 12.1% of patients received human immunoglobulin and 6% received ganciclovir. The average hospital stay was 25.2 ± 12.5 days and 90.9% of patients responded satisfactorily. This study provides relevant information on the clinical profile of congenital CMV infection in order to help improve the management of this type of cases in our hospital.